2013
DOI: 10.1007/s00705-013-1754-z
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Chinese painted quails (Coturnix chinensis) against a highly pathogenic H5N1 avian influenza virus strain after vaccination

Abstract: Chinese painted quails immunized with a single dose (6 μg HA) of inactivated H5N1 (clade 1) influenza vaccine NIBRG-14 and challenged with 100 LD50 of the heterologous A/Swan/Nagybaracska/01/06(H5N1) (clade 2.2) strain were protected, whereas unvaccinated quails died after challenge. No viral antigens or RNA were detected in cloacal swabs from immunized animals. Sera obtained post-immunization gave low titres in serological assays against the vaccine and the challenge viruses. Our results demonstrate the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…We have found similar efficacy with monovalent pandemic H1N1 and prepandemic H5N1 whole virion, aluminum adjuvanted influenza vaccines in adult, elderly, and pediatric patients [ 9 , 17 , 27 ]. As of protection, we previously found in animal studies that the same vaccine dose and formulation is protective in Chinese painted quails (Coturnix chinensis) against Influenza A infection [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have found similar efficacy with monovalent pandemic H1N1 and prepandemic H5N1 whole virion, aluminum adjuvanted influenza vaccines in adult, elderly, and pediatric patients [ 9 , 17 , 27 ]. As of protection, we previously found in animal studies that the same vaccine dose and formulation is protective in Chinese painted quails (Coturnix chinensis) against Influenza A infection [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antigenic stimulation initiates an immune response that involves cellular cooperation, most notably between macrophages, B-lymphocytes and T-lymphocytes. Influenza A is originally an avian virus and, thus, as far as animal models are concerned, using birds to evaluate vaccine effectiveness is theoretically the most logical method [ 21 ]. Even though the EMEA currently also recommends using ferrets for this purpose [ 4 ], for instance, highly pathogenic avian influenza virus (HPAI) strains cause significant mortality in unvaccinated chickens, but their virulence in mammals shows a great degree of variability.…”
Section: Animal Challenge Modelsmentioning
confidence: 99%
“…Such observations indicate that results obtained in HPAI mammalian protection models can vary significantly with the animal species and the dose and type of the experimentally applied challenge virus. It has previously been demonstrated that birds, especially chickens, Japanese quails (Coturnix-japonica), and Chinese painted quail (Coturnix-chinensis) were all useful animal models for testing protection against HPAI [ 21 , 22 ]. Chinese painted quails might be a more suitable model than chickens and Japanese quails in terms of their ease of general care, robustness, reproductive rate, and cost of maintenance [ 21 ].…”
Section: Animal Challenge Modelsmentioning
confidence: 99%
“…Prevention of avian influenza in quails mainly occurs through vaccination combined with implementing biosecurity measures by thorough cleaning and disinfecting and restricting the personal movements on the farm. In a study conducted in China, the protective efficacy of inactivated H5N1 (clade 1) influenza vaccine (NIBRG-14) before challenge with heterologous A/Swan/Nagybaracska/01/06 (H5N1 clade 2.2) strain was tested in quails; the results revealed protection of challenged birds and absence of the virus in cloacal swabs, but immunized birds had low antibody titers (Sarkadi et al, 2013). In Indonesia, it was found that vaccination of brown quails with inactivated bivalent H5N1 clades 2.1.3 and 2.3.2 at ages 24 and 45 days induced significant protection, although the virus shedding continued 7 days post-vaccination (Indriani and Dharmayanti, 2016).…”
Section: Avian Influenzamentioning
confidence: 99%